'She believed in me'. What patients with depression value in their relationship with practitioners. A secondary analysis of multiple qualitative data sets. (18th February 2016) - Percival, John; Donovan, Jenny; Kessler, David; Turner, Katrina
Abstract: Background: Clinical guidance promotes the practitioner–patient relationship as integral to good quality person‐centred care for patients with depression. However, patients can struggle to engage with practitioners and practitioners have indicated that they want more guidance on how to establish effective relationships with their patients. Objective: To identify what practitioner attributes patients with depression particularly value or find problematic. Method: A secondary analysis of data collected during four qualitative studies, all of which entailed interviewing patients diagnosed with depression about their treatment experiences. Patients in the four studies had received different treatments. These included antidepressants, cognitive behaviour therapy, facilitated physical activity and listening visits. We thematically analysed 32 patient accounts. Results: We identified two complimentary sets of important practitioner attributes: the first based on the practitioner's bearing; the second based on the practitioner's enabling role. We found that patients value practitioners who consider their individual manner, share relevant personal information, show interest and acceptance, communicate clearly and listen carefully, collaborate on manageable goals and sanction greater patient self‐care and self‐compassion. It was also evident that patients receiving different treatments value the same practitioner attributes and that when these key practitioner qualities were not evident, patients were liable not to re‐attend or comply with treatment. Conclusion: The practitioner attributes that patients with depression most value have a positive impact on their engagement with treatment. Patients emphasise the importance of a practitioner's demeanour and encouragement, rather than the amount of time or specific treatment a practitioner is able to provide.